PENENTUAN BESARAN NAFKAH MADHIYAH, NAFKAH IDDAH DAN MUT’AH DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA - Ramdani, Riyan; Syafitri, Firda Nisa (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
In navigating the household ark, disharmony cannot be avoided, one of which is the result of neglecting rights and obligations that lead to the breakdown of the marriage. One of the consequences was the burden on the husband to pay for the madhiyah, iddah, and mut’ah livelihoods. The wife has the right to request payment of maintenance to the Religious Court if the husband does not fulfill his obligation to provide for his services. This study aims to discuss the legal basis and considerations of the panel of judges in determining the levels of the amount of madhiyah, iddah, and mut’ah. This study uses normative juridical research to examine statutory regulations related to determining the amount of madhiyah, iddah, and mut’ah. The results showed that First. The basis for determining the amount of income for the former husband is adjusted according to the ability of the husband as stated in Presidential Instruction No. 1 of 1991 concerning KHI, Law no. 1 of 1974, and SEMA No. 3 of 2018 Results of the Plenary of Religion point 2 as the refinement of SEMA No. 7 of 2012 number 16 and Article 149 letter b of the KHI. In the case of divorce talak (Article 8 number (3) letter (c) PERMA No. 3 of 2017) the maintenance of mut’ah and iddah is paid together with the pledge of divorce when pronounced by the Petitioner. Second, the judges’ judgment regarding the determination of the level of the amount of living is based on, a) the wife does not commit nusyuz, b) the economic condition of the husband, c) based on the consideration of the reasonable needs of each party.